Economic Impact Analysis of the Implementation of Agricultural Technology 4.0 on National Food Security - Harsela, Chiska Nova (Politeknik Siber Cerdika Internasional, 2025)
The implementation of Agricultural Technology 4.0 has become an important strategy in facing national food security challenges amidst population growth, climate change, and land limitations. This study aims to analyze the economic impact of the adoption of modern agricultural technologies such as the Internet of Things (IoT), artificial intelligence (AI), and data-driven digital systems on improving production efficiency, distribution, and farmer satisfaction. Using a qualitative approach, data was collected through in-depth interviews, participatory observation, and questionnaires in three key agricultural regions: Sleman, Subang, and Jember. The results show that the use of technology can reduce production costs by up to 30%, significantly increase yields, and expand digital market access. However, challenges such as limited technological literacy and digital infrastructure still constrain implementation. This research confirms the importance of synergy between technology, farmer training and public policy in realizing sustainable food security. The practical implications of this study provide a policy basis to support the overall digital transformation of agriculture in Indonesia.